Cuerpos que narran: la práctica del tatuaje y el proceso de subjetivación (2011)
This article reports the results obtained from a study with a group of tattoo practitioners integrating the sample of subjects interviewed as a part of the project entitled Corporal practices and the construction of self. By means of a Qualitative-interpretative approach, it offers an understanding of the relationship between the corporal practices, the body perception (body concept), the selfcare and the sense of themselves that people build when they link to different forms of corporal practice. The authors approach to an understanding of the way in which persons build their "selves" from their corporal practices, in this case, specifically from tatooing.